2014
DOI: 10.1016/j.jbiomech.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Local dynamic stability of treadmill walking: Intrasession and week-to-week repeatability

Abstract: Repetitive falls degrade the quality of life of elderly people and of patients suffering of various neurological disorders. In order to prevent falls while walking, one should rely on relevant early indicators of impaired dynamic balance. The local dynamic stability (LDS) represents the sensitivity of gait to small perturbations: divergence exponents (maximal Lyapunov exponents) assess how fast a dynamical system diverges from neighbor points.Although numerous findings attest the validity of LDS as a fall r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…In addition, it is very likely that LDS can differentiate among fallers and non-fallers in elderly people [11], [23]. We [24] and others [25] have very recently provided evidence that LDS can be reliably assessed with short walking tests that are suited for patients with low walking capabilities. Two of our recent studies showed that LDS could be used in clinical settings [26], [27].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, it is very likely that LDS can differentiate among fallers and non-fallers in elderly people [11], [23]. We [24] and others [25] have very recently provided evidence that LDS can be reliably assessed with short walking tests that are suited for patients with low walking capabilities. Two of our recent studies showed that LDS could be used in clinical settings [26], [27].…”
Section: Introductionmentioning
confidence: 96%
“…During walking, previous studies in MLE reliability have reported good (i.e., from 0.75 to 0.88) (Portney and Watkins, 2009) intrasession (Kang and Dingwell, 2006b; van Schooten et al, 2013; Reynard and Terrier, 2014; Reynard et al, 2014; Rábago et al, 2015) and moderate (i.e., from 0.53 to 0.68) (Portney and Watkins, 2009) intersession ICC values (van Schooten et al, 2013; Reynard and Terrier, 2014). The ICCs found in our study during walking were clearly higher compared to these previous studies in both intrasession (i.e., from 0.946 to 0.980) and intersession (i.e., from 0.971 to 0.985) comparisons.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in walking conditions reported good intrasession reliability (Kang and Dingwell, 2006b; van Schooten et al, 2013; Reynard and Terrier, 2014; Reynard et al, 2014; Rábago et al, 2015). Based on this, it was argued that differences between young and older adults (Buzzi et al, 2003; Kang and Dingwell, 2008; Terrier and Reynard, 2015; Mehdizadeh, 2017) as well as patients with moderate neurological gait disorders (Reynard et al, 2014) where instability is expected, can be discovered with the MLE.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations